Synthesis of N/Fe Comodified TiO2 Loaded on Bentonite for Enhanced Photocatalytic Activity under UV-Vis Light. - Cao, Xi; Liu, Chen; Yandi Hu; Yang, Wenli; Chen, Jiawei* (Journal of Nanomaterials, 2016)
To improve the efficiency of TiO2 as a photocatalyst for contaminant degradation, a novel nanocomposite catalyst of (N, Fe) modified TiO2 nanoparticles loaded on bentonite (B-N/Fe-TiO2) was successfully prepared for the first time by sol-gel method. The synthesized B-N/Fe-TiO2 catalyst composites were characterized by multiple techniques, including scanning electron microscope (SEM), energy dispersive spectrometry (EDS), X-ray diffraction (XRD), Fourier transform infrared spectra (FT-IR), X-ray fluorescence (XRF), nitrogen adsorption/desorption, UV-Vis diffuse reflectance spectra (DRS), and electron paramagnetic resonance (EPR). The results showed that bentonite significantly enhanced the dispersion of TiO2 nanoparticles and increased the specific surface area of the catalysts. Compared with nondoped TiO2, single element doped TiO2, or unloaded TiO2 nanoparticles, B-N/Fe-TiO2 had the highest absorption in UV-visible region. The photocatalytic activity of B-N/Fe-TiO2 was also the highest, based on the degradation of methyl blue (MB) at room temperature under UV and visible light irradiation. In particular, the synthesized B-N/Fe-TiO2 showed much greater photocatalytic efficiency than N/Fe-TiO2 under visible light, the newly synthesized B-N/Fe-TiO2 is going to significantly increase the photocatalytic efficiency of the catalyst using sun light.